Application Of Peer Teaching Learning Methods To Basketball Free Throw Shooting Learning Outcomes - Jordan Agung Mubarak; Muchamad Arif Al Ardha; Faridha Nurhayati; Dwi Lorry Juniarisca (International Journal of Educational Development, 2024)
PJOK plays an important role in movement activities for students at school. In the learning process, there are learning methods that can be used, one of which is the peer teaching method. PJOK material in junior high school has big ball games, one of which is basketball. This study aims to find out whether the application of peer teaching learning methods can improve basketball shooting free throw learning outcomes. This study used an experimental method with a randomized control group pre-test post-test design. The instruments used in this study are knowledge and skill tests. The study sample used cluster random sampling with class VIII A as the experimental class and VIII E as the control class with a total of 64 students. The results showed that the use ofpeer teachinglearning methods can improve the learning outcomes of shooting free throw basketball grade VIII at SMP.The value of increasinglearning outcomes in the medium category, namely knowledge increased by54.51% and skills by 42.40%.